Bengkel Inggris Program For Enhancing English Potencial - Fitri Ayu; Devi Anggriani; Nizamuddin (The International Conference on Education, Social Sciences and Technology (ICESST), 2023)
The era of rapidly developing scientific and technological progress has opened up opportunities for international communication through English. The study was conducted to analyze the potential of elementary school students in English skills in Klambir Lima Kebun Village. Realizing this reality, the "Bengkel Inggris" program is offered to be one of the solutions. The program further investigates the causes of their difficulties in English. In addition, the " Bengkel Inggris " program is not only a place to learn English but also a place for consultation about English. As a result, there was an increase in both classes as seen from the scores on the pre-test, cycle 1 test and cycle 2 test. In the basic English class, the scores are 65, 73.5 and 89.5 while in the intermediate English class the scores are 65.83, 73 and 88.75. Therefore, it was concluded that English Workshop is a program to improve the English learning achievement of elementary school children in Klambir Lima Kebun.